Introduction of Off-Site Promotion and Enrolment Transaction in Salay Community College - Baclayon, Louella; Padilla, Vincent; Rojoca, Lotes (JPAIR Institutional Research, 2024)
The youth is the hope of the nation. Through educating the youth, a society can thrive for generations. Jean-Jacques Rousseau’s natural education theory is where this study is anchored. This research focuses on the introduction of off-site promotion and enrollment implemented at Salay Community College, Salay, Misamis Oriental, Philippines. This study used grounded theory, specifically thematic analysis research. The study underwent a process and used the Institutional Quality Improvement: Scheming, Attaining, Correcting, and Creating (SACC), which is patterned after the Plan, Do, Check, and Act (PDCA) Cycle Framework. The data was thoroughly documented. The information was gathered through three steps: Open coding, Axial coding, and theory formation. The respondents were three (3) students from each of the three programs (Bachelor of Early Childhood Education (BECED), Bachelor of Technology and Livelihood Education (BTLED), and Bachelor of Science in Entrepreneurship (BS Entrep) who enrolled during the Off-Site Promotion and Enrolment Transaction and the school personnel who conducted and implemented the transaction. The respondents' experiences were taken through individual and focused-group interviews. The result showed that the transaction was instrumental in bringing back the out-of-school youth, school dropouts, and those who stopped because of financial problems. This also resulted in an increased number of enrollees. It is recommended that the transaction be conducted in other municipalities, especially far-flung places, and materials and internet connection should be secured for easy online registration flow.
Keywords: Off-Site Promotion; Enrolment Transaction; Focused-Group; out-of-school-youth; Institutional Quality Improvement; key student informants; key personnel informants; grounded theory; policy development; Philippines